STRATEGI BAURAN PEMASARAN OCTOPUS DIVE PENIDA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN - Ni Wayan Ayu Sekarningsih; I Nyoman Sudiarta; I Putu Sudana (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
Octopus Dive Penida is one of the first local dive centers in Nusa Penida that provides international diving facilities (PADI, ADSI,SSI) with professional instructors. This study discusses the marketing strategy adopted by Octopus Dive. The sample of this research is tourists who have visited and used the services of diving / snorkeling in Octopus Dive Penida. The sample selection technique used purposive sampling with 168 respondents. The technique of collecting data is done in several ways, discussing, observing, interviewing, questionnaires, documentation, and literature study. The data analysis technique was done by quantitative descriptive analysis and SWOT analysis. Resulting in a marketing SWOT strategy from variable marketing mix 7 P that is, SO (Strengths – Opportunities) strategy is doing Brand Positioning as a quality dive operator, doing good relations with the community and improving the quality of Human Resources. WO (Weakness -Opportunities) strategy is to expand business / office locations, educate tourists, re-conduct price analysis and participate in international and national events. ST (Strenghts -Threats) strategy is to innovate services / services for tourists, create dive tourism package programs that don't exist in other dive operators. WT (Weakness -Threats) strategy is to conduct a site analysis to complement offices and innovations in market price adjustments.